Analisa kualitas informasi, kualitas teknikal & fungsional, kualitas keamanan, kemudahan penggunaan mobile aplikasi Gojek terhadap kegunaan, kepuasan dan loyalitas pengguna - Agus Prasetyo Utomo -; Wahyu Arkhamu Razak (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The Gojek Mobile application is one application that is widely used by the wider community. In recent years, Gojek has developed very rapidly and is able to beat conventional transportation modes because it is more practical and has many service features offered by the applicator. This study aims to analyze and determine the extent to which the ease of use, information quality, security quality and technical & functional quality of the Gojek application are perceived as useful for users and have implications for user satisfaction and loyalty. The approach used in this study is included in the type of explanatory research, namely research whose explanation uses hypothesis testing in which the causal relationship between variables is explained. The respondents of this study were 100 students from various universities in the city of Semarang. The data collection technique in this study used a questionnaire instrument where the variables were measured using a five-scale Likert scale, where the data was processed using SmartPLS 3.0. From the model test, the test results show that of the 7 hypotheses, five hypotheses are accepted because they have a significant effect and two are rejected because they are not significant, the data is said to be significant if it has t < 0.05. customer satisfaction variable has a significant effect on loyalty variable with P Values ​​= 0.000, information quality variable also has a significant effect on perceived usefullness variable with P values ​​= 0.001, perceived easy of use variable affects customer satisfaction variable with P Values ​​= 0.000 , the perceived easy of use variable has an effect on the perceived usefullness variable with P Values ​​= 0.009, the perceived usefullness variable affects the Customer satisfaction variable with the P Values ​​= 0.023, the security quality variable has no effect on the perceived usefullness variable with the P Values ​​= 0.085, the technical variable & functional quality has no effect on the perceived usefullness variable with P Values ​​= 0.813.